Development And Analysis Of Hydrotalcite-Modified Porous Membranes For Carbon Dioxide Separation - Wiheeb, Ahmed Daham (2013)
The emission of carbon dioxide (CO2) has become one of the most serious environmental problems since the industrial revolution. Today, reducing CO2 emissions is considered extremely important in order to abate the global climate change and global warming. For this purpose, CO2 separations from gas mixtures have been actively researched. The main objective of this research is to separate CO2 from the synthetically produced gas stream containing binary gas mixtures using inorganic membrane technology. The research focused on the synthesis and development of different porous inorganic membranes modified with hydrotalcite (HT) to facilitate the separation of CO2. Hydrotalcite material was incorporated to improve the CO2 affinity and the thermal stability of the inorganic membranes for CO2 gas separation. The crack free mesoporous HT-alumina (~10 μm) and microporous HT-silica (~200 nm) porous membranes were successfully synthesized on top of γ-Al2O3 layer supported by a α-Al2O3 disc support using the sol-gel and dip-coating techniques. The effect of different parameters on the membrane performance, the structure and permeation properties relationships and the transport mechanism were studied by varying hydrotalcite compositions and sintering temperatures. The unsupported membranes were characterized for the presence of HT, surface functional groups, surface topography and morphology, surface area, pore size, CO2 adsorption and desorption capacity.